IMPLEMENTATION OF PROPHETIC LEADERSHIP IN SHARIA HOSPITALITY INDUSTRY SERVICES IN (Syariah Hotel Solo) - Aditya Firdaus; Fajar Surya Ari Anggara (Islamic Business and Management Journal, 2021)
Leadership is the gift of nature and individual humans given by Allah SWT. Supporting us together with various skills, winning leadership is personal to the next leadership. Leadership role at times the main trigger or litigation process in groups, organizations, institutions and public discussion spaces. However, there are still difficulties in the implementation process. Furthermore, it denies the Islamic teachings that humans are from God who is the leader or caliph. For this reason, every human being has the potential to become a leader.  The most ideal leader in Islam is the Prophet Muhammad SAW. This is because he was able to invite many people in his missionary vision. The leadership model that he did is called the term prophetic leadership or prophetic leadership with various criteria is a must. this prophetic leadership contributes to a deeper and richer understanding of the relationships and responsibilities of leaders and followers because they relate to the quality of decision making and so on. Prophetic leadership itself is adapted from the character of the Prophet, namely: siddiq, tabligh amanah and fathanah. the leadership that the Prophet exemplifies is considered ideal to be applied everywhere. So that in this thesis the author will describe the prophetic leadership that the Prophet exemplified into a hospitality industry company namely Syariah Hotel Solo. With this thesis, it is hoped that it will be useful as an alternative leadership model that can be applied by all Syariah Hotel Solo employees.